The burden and impact of recurrent abdominal pain – exploring the understanding and perception of children and their parents. Issue 1 (31st December 2022) - Bradshaw, Sam; Brinkley, Aoife; Scanlan, Barry; Hopper, Louise
ABSTRACT: Background: Recurrent abdominal pain (RAP) is a common complaint for children and can result in a significantly lower quality of life due to the extent it can interfere with normal life. RAP can also significantly impact the quality of life of parents. This study sought to qualitatively explore parents' and children's understanding and perceptions of the burden and impact of RAP. Methods: Semi-structured interviews were conducted with a sample of parent/child dyads or families ( N = 5) engaging with a psychology service. Findings: The findings of the inductive thematic analysis revealed four emergent themes common to both parents and children: (1) Perception, understanding and identification of RAP, (2) Contributing factors, (3) Coping mechanisms/pain management strategies, and (4) Impact and burden of RAP. Conclusions: These findings have important clinical implications regarding the identification and management of RAP and may also contribute to improving communication between clinicians, parents and children by providing insight from multiple perspectives into how RAP is experienced.